Human Rights by Design: The Responsibilities of Social Media Platforms to Address Gender‐Based Violence Online. Issue 1 (29th September 2018) - Suzor, Nicolas; Dragiewicz, Molly; Harris, Bridget; Gillett, Rosalie; Burgess, Jean; Van Geelen, Tess
Abstract : Gender‐based violence online is rampant, ranging from harassment of women who are public figures on social media to stalking intimate partners using purpose‐built apps. This is not an issue that can be addressed by individual states alone, nor can it be addressed satisfactorily through legal means. The normalization of misogyny and abuse online both reflects and reinforces systemic inequalities. Addressing gender‐based violence online will require the intervention of the technology companies that govern the commercial Internet to prevent and combat abuse across networks and services. We argue that international human rights instruments provide an opportunity to identify with more precision the responsibilities of telecommunications companies and digital media platforms to mitigate harm perpetrated through their networks, and ensure that the systems they create do not reproduce gendered inequality. Finally, we present initial recommendations for platforms to promote human rights and fulfill their responsibilities under the United Nations Guiding Principles on Business and Human Rights.